A toponymic investigation of South African gated communities. Issue 3 (2nd September 2018) - Spocter, Manfred
ABSTRACT: Research into place names has evolved to beyond the encyclopaedic rendition of their etymological and taxonomic foundations. Toponymy was criticized as atheoretical, apolitical and uncritical until the toponymic turn in the latter half of the 1980s and early 1990s. In South Africa, this change can arguably be traced to the mid-1980s with Pirie's insightful treatment of the torturous process of the naming of Soweto. It was until the early 2000s before geographers again took South African toponymy in their sights. This study, focussing on the toponymy of gated communities in non-metropolitan Western Cape, adds to that growing corpus of knowledge by seeking to understand the message that their naming imprints on the urbanscape. The study employs Bourdieu's notion of symbolic capital to illustrate how the naming of gated communities adds to their exclusionary qualities by creating an illusionary residential territory. Private developers use the symbolic capital of naming to market developments thereby creating economic capital. Using a database of gated-community names collected in a previous study it is shown that developments rely heavily on environmental names and names that display elements of community, heritage and links to European locales. The naming conventions point to names symbolizing notions of status and prestige. Interviews with respondents involved in the naming and government officials who consider the names submitted to them point to a situation where there is very little statutory guidance and control over the naming of gated communities. Questions arise as to who contributes to naming in the post-apartheid urbanscape.